Post-Truth, Hoax, dan Religiusitas di Media Sosial - Ulya, Ulya (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2018)
This paper discusses the phenomenon of community religiosity in an era of post-truth that is thick with hoaxes. Post-truth is an era marked by the exclusion of truth and emotion into the motives of action. The rise of internet technology has actually enabled the public to freely convey their ideas, feelings, personal beliefs through social media. Critical discourse method is used to reveal the extent of the impact of hoax for the community while providing alternative solutions. Increasing tensions in the community, religious and community radicalism which are essential are the findings of this paper. Building a social life - diversity that has a mission in the midst of an era like this is very much needed by developing a tradition of religious communities that are aware that real public space cannot be replaced by virtual public space, seeing information based on logic, ethics, and use; examine each information critically, and be open.